The effects of timing, scheme, planting depth and size of the uterine bulbs on the productivity of seed plants and seed quality onions in the conditions of the Foothill zone of the North Caucasus - I. S. Mastyaev; A. F. Agafonov; L. V. Krivenkov; V. A. Podorogin; V. A. Ushakov (Овощи России, 2022)
Relevance. Onion is a valuable food crop, which is due to its chemical composition, taste and medicinal qualities. As part of the strategy to ensure food security and independence of Russia in the agricultural sector, it is necessary to increase the production of vegetable products, including onions, and for this it is necessary to increase the production of domestic seeds. Seed production is an important branch of agriculture, which consists in the planned reproduction of zoned varieties. Unlike commodity production, it is a more labor-intensive industry and requires regular improvement of existing technologies that take into account the specifics of new varieties and hybrids.Materials and methods. The object is onion (Allium сера L.). Research material: new varieties of spring onion Primo and Ampex of selection of FSBSI FSVC. The studies were conducted in 2018-2020 on the basis of the North Caucasus branch of the FSBSI FSVC. Laboratory and field experiments were carried out according to generally accepted methods. The area of the accounting plot is 5m2 , the repetition is 4-fold, with a randomized arrangement of options.Results and discussions. Different planting dates of uterine bulbs, their diameter, standing density, planting depth, significantly affected the qualitative and quantitative indicators of seed productivity of onion plants of Primo and Ampex varieties. The results obtained made it possible to modify and optimize individual elements of varietal technologies of onion seed production. To create the best conditions for the growth and development of seed plants of Ampex and Primo varieties and to obtain high yields of high-quality seeds in the conditions of the foothill zone of the North Caucasus, it is recommended to: use queen bulbs of 8 cm in size, organize the planting of queen bulbs in the first decade of November, use a scheme for planting queen onions: 75x10 cm, use a planting depth of 15 cm. With this technology, the productivity of plant seeds reaches 6-8 g in the Ampex variety and 5-7 g in the Primo variety, and the yield of conditioned seeds is 520-580 kg/ha and 450-600 kg/ha, respectively.